Utilization of fermented glutinous rice as starting material for carbon nanotubes synthesis using thermal-CVD / Nik Farhana Samsudin - Samsudin, Nik Farhana (2012)
A new approach of starting material for CNTs preparation has been introduced in this research. The fermentation conditions of glutinous rice have been optimized to ensure it was suitable to be used in Two-system Thermal Chemical Vapor Deposition(Thermal CVD) method. The prepared CNTs were characterized using Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and Raman spectroscopy. In optimizing the fermented glutinous rice, inoculum amounts were varied from 1 - 11 wt. % of the glutinous rice, meanwhile the incubation time was ranged from 2 to 8 days period. Incubation temperatures were examined from 10°C up to50°C. It was concluded that the optimum inoculums amount in fermented glutinous rice for CNTs synthesis was 1 wt. % and it should be inoculated for 2 days at 30°C of incubation temperature. As such, the optimized fermented glutinous rice was further used for the optimization of Thermal CVD system. Furnace 1 was ranged from 300°C to500°C with 50°C interval, meanwhile furnace 2 temperature was examined from 600°Cto 900°C with the same interval. The fermented glutinous rice was fully vapored at450°C in furnace 1, meanwhile the deposition temperature (furnace 2 temperature) was best at 750°C. Catalyst preparation also plays an important role for CNTs synthesis. Three types of catalyst preparation was introduced; Seeded, Floated and last but not least Seeded-Floated preparation. Nickel was used as Seeded catalyst as it was reported to be the fastest metal catalyst diffused by carbon thus had promoted the catalytic activity and carbon segregation in CNTs synthesis. Meanwhile ferrocene was used for Floated catalyst preparation due to its volatile organometallic complex which was suitable to make CNTs in large scale using CVD method.